2020
DOI: 10.3390/en13153757
|View full text |Cite
|
Sign up to set email alerts
|

Smart Energy Solutions as an Indispensable Multi-Criteria Input for a Coherent Urban Planning and Building Design Process—Two Case Studies for Smart Office Buildings in Warsaw Downtown Area

Abstract: The introduction of parametric tools has made a strong shift within a traditional approach to urban planning and building design, including the creation of a design awareness zone where environmental issues are concerned. This approach also uses sufficient data to be used already at the concept stage and provides initial interdisciplinary solutions. Analyses from the very initial stages allow the inclusion of smart energy choices influencing the massing, architectural features, proportions, flexibility of desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Parametric tools have a considerable impact at the concept stage [27][28][29] on developing design awareness regarding environmental issues in building design and urban planning for providing initial interdisciplinary solutions [34]. The study identifies Antoni Gaudí, Frei Otto, and Sergio Musmeci as pioneers of the use of gravity modeling as the single independent parameter in the analysis of structural shapes.…”
Section: Collaboration Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parametric tools have a considerable impact at the concept stage [27][28][29] on developing design awareness regarding environmental issues in building design and urban planning for providing initial interdisciplinary solutions [34]. The study identifies Antoni Gaudí, Frei Otto, and Sergio Musmeci as pioneers of the use of gravity modeling as the single independent parameter in the analysis of structural shapes.…”
Section: Collaboration Toolsmentioning
confidence: 99%
“…The study identifies Antoni Gaudí, Frei Otto, and Sergio Musmeci as pioneers of the use of gravity modeling as the single independent parameter in the analysis of structural shapes. Their analysis included algorithmic models that dealt with building form optimization, urban scale, sun radiation levels, shadow, and wind analyses, indicating the use of solar and wind energy as alternative energy sources [34].…”
Section: Collaboration Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary energy (PE) was accepted as the preferable parameter and calculated as the final energy multiplied by the chosen energy carrier's non-renewable primary energy input coefficient wi. For electric energy, the wi coefficient equals 3.0, and for the Warsaw heating network, it is 0.79 [39]. The total primary requirement for the designed building was estimated at 5,127,843.01 kWh/year and a PE ratio of 412.85 kWh/m 2 year.…”
Section: Generalitiesmentioning
confidence: 99%
“…Architects need more tools that can help them during the decision process in the area of sustainable design as "analyses from the very initial stages allow the inclusion of smart energy choices influencing the massing, architectural features, proportions, flexibility of design, and economics" [4]. It has been observed that architecture students, when assisted with a tool that can facilitate their understanding of the effect their choices exert on the environment, create better architectural designs in terms of global warming and other environmental impacts [5].…”
Section: Figurementioning
confidence: 99%